Mitochondrial CPT1A: Insights into structure, function, and basis for drug development - Liang, Kai (Frontiers in Pharmacology, 2023)
Carnitine Palmitoyl-Transferase1A (CPT1A) is the rate-limiting enzyme in the fatty acid β-oxidation, and its deficiency or abnormal regulation can result in diseases like metabolic disorders and various cancers. Therefore, CPT1A is a desirable drug target for clinical therapy. The deep comprehension of human CPT1A is crucial for developing the therapeutic inhibitors like Etomoxir. CPT1A is an appealing druggable target for cancer therapies since it is essential for the survival, proliferation, and drug resistance of cancer cells. It will help to lower the risk of cancer recurrence and metastasis, reduce mortality, and offer prospective therapy options for clinical treatment if the effects of CPT1A on the lipid metabolism of cancer cells are inhibited. Targeted inhibition of CPT1A can be developed as an effective treatment strategy for cancers from a metabolic perspective. However, the pathogenic mechanism and recent progress of CPT1A in diseases have not been systematically summarized. Here we discuss the functions of CPT1A in health and diseases, and prospective therapies targeting CPT1A. This review summarizes the current knowledge of CPT1A, hoping to prompt further understanding of it, and provide foundation for CPT1A-targeting drug development.